Analisa Kekuatan Bracket Pada Kapal Ro-Ro Menggunakan Aplikasi Finite Element - Alamsyah Alamsyah; Amalia Ika Wulandari; Bimo Harseno Ramadhan (SPECTA Journal of Technology, 2020)
In the transverse frame of the ferry ro-ro, there is a construction of the amplifier called the bracket contained on the car deck. The bracket construction functions to connect 2 (two) other constructions such as transferred deck beam and frame. The purpose of this study is to determine the strength of the bracket against the maximum work stress that occurs after being compressed. The method used is a finite element analysis with the help of finite element based applications. On the bracket, modulus optimization will be carried out to approach yield strength after being subjected to deck loads and ship side loads. The results showed that the solid bracket had a modulus of wsolid = 1485.168 cm3, while the cross-section modulus of the bracket with a circle hole diameter 60 mm w60 = 1463.973 cm3, a bracket with a circle hole diameter 70 mm was w70 = 1451.511 cm3, and a bracket with a diameter circle hole 75 mm is w75 = 1443.771 cm3. Maximum working stress that occurs in solid brackets is σmax solid = 92.0871 N/mm2, with holes 60 mm ie σmax d60 = 96.6237 N/mm2, and with holes 70 mm ie σmax d70 = 155.999 N/mm2, does not exceed yield stress (σmax < σy = 250 N/mm2). While the bracket tension with the hole 75 mm is σmax d75 = 272.861 N/mm2, exceeding the yield stress (σmax < σy = 250 N/mm2). So that the perforation on bracket construction can be done only on diameter sizes d = 60 mm and 70 mm. This information can minimize the use of steel material that has an effect on the ship's steel weight calculation.